Students’ Need on Speaking Classroom Activities as the Basis of Developing Project Based Learning Model (Conference on English Language Teaching, 2023)
English in higher education context is crucial because it linguistically supports the occupational nature in education when carried out accurately or, principally, specifically. In this area, speaking as one of the English skills is used as the approach to prepare students with English language skills related to their majors. The purpose of this research is then to determine the profile of speaking competencies performed by students and their needs  on  classroom  activities  which  may  support  their  speaking  skill.  Case  study  is selected as the research method, utilizing several data collection methods, namely: needs analysis questionnaire administered to 60 English Education Department (TBI) students in UIN SMH Banten who had experienced academic speaking subject; interviews held with ten selected students, and several documents, namely: the lesson plans, and the textbook used in the course. From the gathered data, the speaking classroom activities which met the students’ needs are primarily required students to get involved actively in discussion and presentation on certain topic.